Studi Komparatif Terhadap Pelaku Main Hakim Sendiri (Eigenrichting) yang Menyebabkan Kematian Menurut Hukum Pidana Islam dan Hukum Pidana - Zari; Syaiful Munandar (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2024)
The act of vigilantism in Dutch Eigenrichting is an arbitrary act carried out by the community against the perpetrator of a crime by torturing, beating, and even burning the victim which causes injuries and death. This act of taking the law into your own hands has become an act that continuously occurs in people's lives. This action creates new problems and also violates human rights where perpetrators of crimes have the right to receive defense by the authorities and be punished according to established regulations. In Islamic criminal law (jinayah) the act of taking the law into your own hands is included in the act of semi-intentional murder (al-qatl Syibh al-'Amd) where the sanctions for this act are diyat, kiffarat and additional punishment. In positive criminal law, the Criminal Code explains in articles 351-358 about abuse and the forms of this act. The problem in this research is the determination of the sanctions for vigilantism perpetrators in Islamic criminal law and positive criminal law, as well as the distinctions between the two legal systems. A normative method is employed in this research, which involves the examination of books, scientific works, and legislation that are pertinent to the issue. This research discusses “how the firmness of law in Indonesia regulates perpetrators of vigilante actions that cause death, and a comparison with Islamic criminal law which is the majority religion in Indonesia”.